Cluster ambidexterity towards exploration and exploitation: Strategies and cluster management - Wolf, Tina (Springer Nature, 2020)
Cluster studies have shown that innovation often results from an inter-organizational process, where a division of labor with regard to exploration and exploitation exists among the actors inside a cluster. A cluster is ambidextrous if it manages to balance innovative activities that exploit existing competencies and is open to novel technological approaches by means of exploration. In this context, we are interested in the supportive role of cluster management, assuming that a cluster organization can only persist sustainably if exploitation and exploration are pursued in an appropriate balance. Our analysis is based on surveys conducted between 2011 and 2012 with ten cluster managements and their respective cluster ﬁrms of the ﬁrst two waves of the German Leading Edge Cluster Competition. Our results indicate that the demand for services offered by the cluster management depends on companies’ strategies with respect to exploration, exploitation, and ambidexterity. In turn, the priorities set by the cluster management can be explained by the ﬁrms’ needs. Accordingly, we argue that cluster management acts as a service provider, helping the cluster companies to become ambidextrous which, in turn, makes the cluster as a whole ambidextrous.